Adolescents' inhaled corticosteroid adherence: the importance of treatment perceptions and medication knowledge. (May 2015) - Koster, Ellen S.; Philbert, Daphne; Winters, Nina A.; Bouvy, Marcel L.
Abstract Background: Studies measuring inhaled corticosteroid (ICS) adherence frequently report adherence rates below 50%. Although asthma is common in adolescents, few studies have explored determinants of ICS adherence in adolescents. The objective of this study was to examine adherence and related factors in adolescent ICS users. Methods: Adolescent ICS users, aged 12–18 years, were randomly recruited from a sample of 94 community pharmacies belonging to the Utrecht Pharmacy Practice Network for Education and Research to complete an online questionnaire. The survey contained questions on asthma control, self-reported adherence, medication beliefs and medication knowledge. Data were collected between April and August 2013. Results: Complete questionnaire data were received from 182 adolescents of which 40% reported to be adherent. Approximately 40% of the participants perceived strong needs, whilst only 10% was highly concerned about adverse effects regarding their ICS use. Good adherence was significantly associated with asthma control (OR: 2.1, 95% CI: 1.1–4.1). Necessity beliefs and sufficient medication knowledge were associated with better adherence (p < 0.05). Conclusion: Our results suggest that by improving knowledge about asthma treatments and stimulating positive perceptions towards medicines, especially regarding the necessity of medication use, better adherence rates might be achieved.